Kafa'ah al-Mu'allimin fi Istikhdam Barnamij VLE Frog al-Ta'limiy fi Ta'lim al-Lughah al-Arabiyyah fi al-Madaris al-Ibtida'iyyah fi Kuala Lumpur - Abdul Halim, Rosmani; Sahrir, Muhammad Sabri (Penerbit UPSI, Perak Darul Ridzuan., 2021)
A book chapter published by UPSI Press 2021.